Pathways From Family Violence to Adolescent Violence: Examining the Mediating Mechanisms - Li, Spencer D.; Xiong, Ruoshan; Liang, Min; Zhang, Xiaohua; Tang, Wei (Frontiers in Psychology, 2021)
Purpose: Past research has documented a significant relationship between family violence and adolescent violence. However, much is unknown about the processes through which this association occurs, especially in the non-Western cultural context. To address this gap, we propose an integrated model encompassing multiple pathways that connect family violence to adolescent violence. Specifically, this study investigates how family violence is related to adolescent violence through violent peer association, normative beliefs about violence, and negative emotions. Method: We tested the model using the two-wave survey data collected from a probability sample of more than 1100 adolescents residing in one of the largest metropolitan areas in China in 2015 to 2016. Results and Conclusions: The results indicated that family violence predicted adolescent violence perpetration. Violent peer association, normative beliefs and negative emotions, however, mediated much of the relationship between family violence and adolescent violence.